4,10-Diallyloxy-1,2,3,6b,7,8,9,12b-octahydroperylene - Smith, T.D.; Mahindaratne, M.P.D.; Penick, M.A.; Negrete, G.R.; Daniels, L.M.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C(26)H(28)O(2), the central atoms are coplanar, with the -CH(2)-CH(2)- links of the cyclohexene groups lying to either side of the plane and with the diallyloxy residues twisted out of this plane [C-C-O-C torsion angles = 16.6 (3) and -13.9 (3)degrees]. In the crystal structure, molecules are connected into chains propagating in [100] via C-H center dot center dot center dot pi interactions.